PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT TUNGGAL PERKASA PLANTATION KABUPATEN INDRAGIRI HULU - Trisna, Miranda; Susi, Hendriani; Kurniawaty, fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of leadership and compensation on employee performance through job satisfaction of employees at PT. Tunggal Perkasa Plantation Indragiri Hulu Regency. The population in this study included employees in the field of PT. Tunggal Perkasa Plantation, Indragiri Hulu Regency, amounting to 110 people. Primary data is collected by questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study is to use path analysis (path analysis) with the help of the SPSS program. The sampling technique that has been chosen is the census method (110 employees at PT. Tunggal Perkasa Plantation Indragiri Hulu Regency) The results showed that: 1) there is a positive and significant influence of leadership on employee performance, 2) there is a positive and significant effect of compensation on employee performance, 3) there is a positive and significant influence of employee job satisfaction on employee performance, 4) there is influence positively and significantly leadership on employee performance through employee job satisfaction, 5) there is a positive and significant effect of compensation on employee performance through employee job satisfaction.Keywords : Leadership, Compensation, Employee Performance, and Work Satisfaction